Markup and market power in the Malaysian manufacturing industries. - Hassan, Azman; Samsi, Aznita; Law, Siong Hook; Mohamed Noor, Norashidah (IUP Publications, 2008)
This article examines the market power in 3-digit Malaysian manufacturing industries, using cross-sectional data. Measure of market power is one of the primary concerns of industrial organization economics, because it can provide valuable information for the design of public policy towards monopoly and anti-competitive parties. Markup ratio of price over marginal cost is an indicator for assessing the degree of market power. Hall's model was applied to document the disparity between price and marginal cost. The results indicated that the Malaysian manufacturing industries at 3-digit level have market power, and are thus in need of a competitive policy to check the abuse of market power.